Three times table - Maitland, Sara (London : Virago, 1991)
A novel about three women who share a house but inhabit different worlds. Maggie is 15 and flies with her dragon to a secret world. Her mother has carried her 60s values into the harsh 80s, and the grandmother, a paleontologist, has to reconsider theories she has always fought for.
Keywords: Mothers and daughters -- Fiction; Middle-aged women -- Fiction; Imaginary creatures -- Fiction